Keefektifan Model Pembelajaran Role Playing Terhadap Peningkatan Interaksi Sosial Siswa Kelas 4 SDN Bumiayu 2 Malang - Aldy Ferdiyansyah; Siti Latifa Zahara; Wahyu Puji Rahayu; Muhammad Alfan; Shirly Rizki Kusumaningrum; Aldy Ferdiyansyah; Siti Latifa Zahara; Wahyu Puji Rahayu; Muhammad Alfan (Universitas Negeri Malang, 2021)
Abstract: This research was conducted with the aim of testing effectiveness using the role playing learning model on increasing the social interaction of 4th graders at SDN Bumiayu 2 Malang. This study uses a pre-experimental design method with a quantitative approach. The results of the calculation of the paired sample test show a significance value of 0.000 which is less than 0.05. So that it can be interpreted that there is a significant difference between the results of the pretest and posttest, in other words the use of role playing models has an effect on increasing students' social interactions. The level of effectiveness of the use of the role playing model is included in the medium category based on the results of the N-Gain test with an average gain score of 0.6. Abstrak: Penelitian ini dilakukan dengan tujuan menguji efektivitas penggunaan model pembelajaran role playing terhadap peningkatan interaksi sosial siswa kelas 4 SDN Bumiayu 2 Malang. Metode penelitian yang digunakan yaitu pre-experimental design dengan pendekatan kuantitatif. Hasil dari penghitungan uji paired sample test yang menunjukkan nilai signifikansi sebesar 0,000 yang bernilai kurang dari 0,05. Sehingga dapat diartikan bahwa terdapat perbedaan yang signifikan antara hasil dari pretest dan posttest, dengan kata lain penggunaan model role playing berpengaruh dalam peningkatan interaksi sosial siswa. Tingkat efektivitas dari penggunaan model role playing termasuk dalam kategori sedang berdasarkan hasil uji N-Gain dengan rata-rata gain score sebesar 0,6.